Karakteristik Hasil Co-Pyrolysis dari Limbah Plastik dan Oli Bekas - Kamal, Dianta; Heryana, Ghany (Jurnal Teknik Mesin dan Mekatronika (Journal of Mechanical Engineering and Mechatronics), 2024)
This study aims to utilize low-density polyethylene (LDPE) plastic waste and used engine oil to produce alternative liquid fuel through the co-pyrolysis method. The co-pyrolysis process was carried out with various ratios of LDPE plastic waste and used engine oil, specifically 5:0, 5:1, 5:2, 5:3, and 5:4, within a temperature range of 165°C to 177°C for 1 hour. The characteristics of the resulting liquid products were tested to determine their calorific value, density, and viscosity. The results showed that the calorific value increased with the addition of used engine oil, reaching 11,061.67 cal/g at a 5:4 composition. The liquid products had an average density of 0.8686 g/mL, which was within the range of diesel fuel density. The viscosity of the liquid products also met gasoline standards, with an average value of <1 cSt. The highest yield efficiency reached 9.14 mL/kWh at a 5:4 composition with an efficiency of 1.93%, indicating significant potential in producing energy-efficient liquid fuel. This study sheds new light on the use of plastic waste and engine oil as environmentally friendly alternative liquid fuels.